2006
DOI: 10.1093/intimm/dxl132
|View full text |Cite
|
Sign up to set email alerts
|

Th1 cell adjuvant therapy combined with tumor vaccination: a novel strategy for promoting CTL responses while avoiding the accumulation of Tregs

Abstract: We have previously described a method for adoptive immunotherapy of cancer based on antigen-specific T(h)1 cells. However, efficient induction of anti-tumor responses using T(h)1 cells remains a formidable challenge, especially for MHC class II-negative tumors. In the present study, we sought to develop a novel strategy to eradicate established tumors of the MHC class II-negative, ovalbumin (OVA)-expressing EG-7 cells. Tumor-bearing mice were intradermally treated with OVA-specific T(h)1 cells, combined with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…These findings indicate that the model cancer vaccine is shifting the balance from a tolerogenic to an immunogenic microenvironment in the tumor. Similarly, other studies have found that Tregs infiltrated the tdLN less when targeted with a cellular therapy in tumor-bearing mice (44).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These findings indicate that the model cancer vaccine is shifting the balance from a tolerogenic to an immunogenic microenvironment in the tumor. Similarly, other studies have found that Tregs infiltrated the tdLN less when targeted with a cellular therapy in tumor-bearing mice (44).…”
Section: Discussionmentioning
confidence: 65%
“…4B) induced by targeting the vaccine to the tdLN led to regression of early-stage tumors and more impressively of tumors having reached the Swiss legal limit of 1 cm 3 . In the literature, cancer vaccines are usually administered when the tumors are 5 to 7 mm in diameter or even before they are detectable, and also do not usually induce this high number of TAA-specific CD8 þ T cells in the blood and the LNs (17,19,30,38,44), thus emphasizing the benefits of nanoparticle-mediated targeting of antigen and adjuvant to DCs in the tdLN (18,38,45). We noted, however, that after regressing some tumors grew back.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, our results indicate that IL-17-producing gd T cells act as pro-but not anti-tumor effector cells in tumorgrowing microenvironment. In our previous work [16][17][18][19][20], we have proposed that the introduction of Th1-dominant immunity overcomes strong immunosuppression in tumor-bearing host and induces complete cure of the tumor-bearing mice. Therefore, we now investigated whether Th1 cell therapy or introduction of Th1 immunity by IL-12 can induce a plasticity in IL-17-producing gd T cells, namely, alter pro-to anti-tumor IL-17-producing gd T cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have proposed that the induction of Th1-dominant immune responses is an essential step in inducing strong anti-tumor immunity in response to adjuvants or tumor-specific Th1 cells [16][17][18][19][20]. However, within the tumor microenvironment, the balance between IL-12 and IL-23, which directly reflects Th1 and Th17 cell responses, is shifted toward IL-23 via activation of STAT3 [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have proposed that tumour-specific CD4 þ T cells, especially T-helper type 1 (Th1) cells play a critical role for inducing cytotoxic T lymphocytes (CTL)-mediated antitumour immunity in tumour-bearing mice Ikeda et al, 2004;Chamoto et al, 2006;Zhang et al, 2006). Although many investigators have centred in the activation and targeting of tumour-specific CD8 þ CTL and CD4 þ T cells are required for the priming and maintenance of CD8 þ T cells (Janssen et al, 2003;Smith et al, 2004;Sun et al, 2004).…”
mentioning
confidence: 99%